DYNAMICS OF TARJIH MUHAMMADIYAH AND ITS CONTRIBUTIONS ON THE DEVELOPMENT OF ISLAMIC LAW IN INDONESIA - Kholidah Kholidah (Proceeding International Seminar of Islamic Studies, 2021)
This dissertation aims to; 1) analyzing the dynamics of tarjih in responding to problems that arise in society; 2) analyzing the dynamic pattern of tarjih and 3) evaluating the contribution of tarjih products to the development of Islamic law in Indonesia. This research is a qualitative, type of literature. The data source is taken from Tarjih's decision and writings related to Tarjih. Data were collected through documentation as well as interviews as a complement. The data were analyzed using content analysis, using a sociological-historical approach. Conclusion; first, the dynamics of tarjih in responding to developing problems can be seen in three aspects; a) institutional aspects, there is changes in the nomenclature, organizational structure, requirements for tarjih members and tarjih implementation. b) Manhaj aspect, there are five stages of development, 1) 1928), 2) 1954/1955, 3) 1986, 4) 2000 and 5) 2018. c) In the product aspect, tarjih is dynamic in assessing problems and there are three forms of product. Second, the dynamic pattern of tarjih follows an evolutionary pattern, is multilinier, follows many pathways that influence each other and occur due to changes in society. Third, tarjih contributes to the development of Islamic law in Indonesia, normatively and positively.Keyword: Dynamics, Tarjih, Contribution